A Context-Appropriate Approach to Marine 14C Calibration: Δr and Bayesian Framework for the Nuvuk Cemetery, Point Barrow, Alaska. Issue 3 (23rd April 2019) - Krus, Anthony M; Jensen, Anne M; Hamilton, W Derek; Sayle, Kerry
ABSTRACT: This study provides an assessment of the temporal changes in ΔR, which is the local deviation from the global surface water marine reservoir effect (MRE), in the Point Barrow area of the Alaskan Arctic, a coastal archaeological area that has experienced severe erosion accelerated by global warming. A total of 26 samples were submitted for radiocarbon ( 14 C) dating from eight secure Thule (AD 1000–1750) archaeological contexts, and specifically from archaeological features with paired processed seal and caribou bones that had been frozen in situ . This new approach towards ΔR estimation provides a best-fit local correction for the 14 C dating of human populations by focusing on the marine mammal (seals) predominantly consumed by the Thule (Coltrain et al.2016 ). The weighted-mean ΔR value on these pairs is 450 ± 84 yr, which is about 50 years less than the weighted-mean (506 ± 69 yr) for the Point Barrow area calculated through 14 C measurements from four known-age bivalves collected in AD 1913 (McNeely et al.2006 ). The effects of using this new ΔR value for calibration was assessed through the Bayesian chronological modeling of 54 14 C measurements from samples of human skeletons interred in the Nuvuk cemetery at Point Barrow, the largest ancient cemetery in northwest Alaska and traditionally thought to date to the Thule and earlier Birnirk (AD 500–1000) periods.